FRAGILITY FRACTURES IN BRAZIL: CROSS-SECTION STUDY - Cocco,Luiz Fernando (2022)
ABSTRACT Objective: To evaluate the involvement of orthopedists and orthopedic residents with fragility fractures, in its clinical, therapeutic, and social aspects. Methods: Cross-sectional observational and prospective study that took place in the period from June to August 2020. Results: 540 participants were analyzed. The population consisted of orthopedists (85.56%; N = 462) and residents (14.44%; N = 78), with a greater proportion of individuals from 41 to 50 years of age (36.67%; N = 198) and from the Southeast region (57.22%; N = 309). For 47.04% (N = 254) of the participants, the profile of the patient at risk for fragility fracture corresponds to: woman, sedentary, smoker and over 60 years of age. The consensus among the participants (97.96%; N = 529) is that fragility fractures occur in or near home environments. Moreover, 47.59% (N = 257) believe that the first fragility fracture is the most important predictive risk factor for subsequent occurrences and 63.89% (N = 345) of the participants claim to attend more than 15 cases per year. Regarding treatment, 74.44% (N = 402) are dedicated exclusively to orthopedic aspects (68.33%; N = 369). However, 62.41% (N = 337) of the participants believe that patients with fragility fractures should receive medication and supplements. Likewise, 70.74% (N = 382) of the participants consider that home security measures and training of family members are important, and they attribute the role to the multidisciplinary team. Conclusions: Fragility fractures are frequent in the routine of Brazilian orthopedists. However, they are not familiar with adjuvant treatments for fragility fractures, acting almost exclusively in the orthopedics aspects of these injuries. Level of Evidence II, Prospective Study.